MOBILE SHOPPING: TRENDS, CHALLENGES, AND OPPORTUNITIES IN E-COMMERCE - Palande, Pandit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
he emergence of mobile commerce (m-commerce) has revolutionized the shopping patterns of consumers through the growing usage of smartphones, artificial intelligence-powered personalization, augmented reality (AR), and blockchain. Organizations are quickly incorporating these technologies to build consumer relationships and trust. Nevertheless, areas such as security issues, consumer trust, and the efficacy of rebranding in enhancing the perception and loyalty of brands remain pertinent areas of research. The study investigates consumer trends in mobile buying, the effect of new technology, and rebranding and its influence on customer loyalty. A quantitative research design was utilized, and data were collected from 400 respondents in Pune city using a structured questionnaire. Regression Analysis and ANOVA were applied in SPSS to test hypotheses regarding the impact of AI, AR, and blockchain on consumer engagement and rebranding strategies on brand loyalty. Findings reveal that, although new technology has a favourable effect on consumers’ engagement and mobile shopping experience, demographic differences have no tangible impact on shopping behaviour via the mobile phone. No meaningful linkage was also reported between rebranding efforts and loyalty, but this could reflect the fact that product quality, price competitiveness, and customer services matter more in the equation. The research finds that companies have to invest in AI-based personalization, AR, and blockchain technology but with the aspect of ease of use and accessibility. Moreover, instead of just focusing on rebranding, companies should be going for end-to-end approaches with focus areas in consumer-oriented strategies, building trust, and improved shopping experience. Future research could investigate regional differences, rates of adoption of emerging technologies, and regulatory issues in mobile commerce.